PERAN PEMBERDAYAAN EKONOMI MELALUI SKIM QARDHUL HASAN TERHADAP PENGEMBANGAN USAHA MUSTAHIQ (STUDI KASUS PADA AL-AZHAR PEDULI UMAT) - Herlambang, Leo; Cahyono, Eko Fajar; Widiastuti, Tika (IQTISHODUNA, 2015)
The purpose of this study was to determine the role of economic empowerment throughqardhulhasanâ€™ skim against mustahiq business development at Al Azhar Caring Ummah (APU Foundation).Â  QardhulHasanis a financial product for micro businesses that do not provide financial benefits for the lender.Qardhulhasanfunds managed Al Azhar Care for People (APU Foundation) came from zakat, infaq, charity Islamicbanking.Economic empowerment of Al Azhar that carried the People Concerned role in business developmentprogram mustahiq dam frame a million defenseless. The program use to improve the local economy and buildmicro-economic resilience and make bankable for the mustahiq